2014
DOI: 10.4236/psych.2014.58106
|View full text |Cite
|
Sign up to set email alerts
|

Description of the General Procedure of a Stress Inoculation Program to Cope with the Test Anxiety

Abstract: We set out the stages in the general procedure of a stress inoculation program for the treatment of test anxiety in university students, with the aim of adapting it to the characteristics of each participant. Research has previously been conducted to that end (Serrano, Delgado, & Escolar, 2010; Serrano, Escolar, & Delgado, 2002; Serrano, Escolar, & Delgado, 2011) on dismantling strategies in a real clinical field. We conclude that there are individual response patterns to test anxiety, so it is therefore neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…The stress inoculation technique is already utilized in many high-stress job training programs, such as training for first-responders and medical staff. It also has been shown to be effective in other conditions as well, such as preventing PTSD in military members, anxiety and depression in cancer patients, or even to reduce exam anxiety in stressed-out students (107,109). In the future, we will be able to more accurately monitor an individual for stress coping and resilience by combining information from self-reported measures, vital sign and demographic data, psychosocial, stress reactivity, genomics, proteomics, transcriptomics, metabolomics, and epigenetics to apply more of a comprehensive systems approach to diagnosis and treatment of stress induced disorders.…”
Section: Future Directions and Resilience Interventionsmentioning
confidence: 99%
“…The stress inoculation technique is already utilized in many high-stress job training programs, such as training for first-responders and medical staff. It also has been shown to be effective in other conditions as well, such as preventing PTSD in military members, anxiety and depression in cancer patients, or even to reduce exam anxiety in stressed-out students (107,109). In the future, we will be able to more accurately monitor an individual for stress coping and resilience by combining information from self-reported measures, vital sign and demographic data, psychosocial, stress reactivity, genomics, proteomics, transcriptomics, metabolomics, and epigenetics to apply more of a comprehensive systems approach to diagnosis and treatment of stress induced disorders.…”
Section: Future Directions and Resilience Interventionsmentioning
confidence: 99%
“…In a recent review, Markiewcz (2017) showed that neurofeedback is effective in many psychiatric disorders that affect psychological variables such as stress and anxiety. To avoid the side effects of drugs, from the perspective of anxiety-reducing technology (Pintado and Llamazares, 2014), neurofeedback therapy is a promising new method with stable and lasting therapeutic effects no side effects.…”
Section: Introductionmentioning
confidence: 99%
“…The Teacher Test Anxiety (TTA) inventory was developed based on existing instruments (e.g., Fujii, 1993;Serrano-Pintado & Escolar-Llamazares, 2014;Mowbray, Jacobs & Boyle, 2015). The 12-item TTA consist of three items -general test worrying, test irrelevant thinking, and negative emotions as shown in Table 1.…”
Section: Teacher Exam Anxiety Inventorymentioning
confidence: 99%